Gender Research Strategy for Phase II (2017-2022): CGIAR Research Program on Climate Change, Agriculture and Food Security (CCAFS) - CGIAR Research Program on Climate Change, Agriculture and Food Security (2016)
Gender research has substantially influenced the direction of CCAFS in all four areas identified by Lipper et al (2014) (see Section 1.0.4), as well as in FPs. Gender research in Phase I included: modelling yield gaps to identify and prioritize adaptation measures that benefit women farmers (2014); baseline surveys in all CCAFS sites that include a gender component (2013); systematic review of gender issues in climate risk management and gender-disaggregated field-based analysis of local use of climate information (2012); and training, models, tools and approaches to collect gender and social differentiated information on climate analogues, climate information, institutions, mitigation, and adaptation and risk (2011).